Genômica aplicada à reprodução equina - Leon, Priscila Marques Moura de (2011)
In equine, the intersections between reproduction and genomics are numerous, however, little known about the genetic factors that acting on fertility. The conclusion of equine genome sequencing project, brings the oportunity to evaluate candidate genes and molecular biomarkers for specific reproductive characteristics. Based on this information, this PhD thesis aimed to develop genomic studies applied to equine reproduction. The first paper analyzed the expression of apoptotic-related genes (Bax, Bcl-2, survivin and p53) in equine cumulus-oocyte complex by qRT-PCR, comparing gene expression between morphologically distinct oocytes and cumulus cells during in vitro maturation. Results showed that survivin mRNA levels were higher (P<0.05) and p53 mRNA levels was lower (P<0.01) in oocytes compared to cumulus cells in morphologically healthy. On the other hand, expression of the Bax was significantly higher in morphologically healthy cumulus cells (P<0.02). The second paper analyzed a single nucleotide polymorphism (SNP) in the p53 gene, looking for associations with reproductive parameters in Thoroughbred mares. This is the first study demonstrating the Arginine/Proline SNP in equine exon 4 p53 gene. The heterozygous Arginine/Proline was found in 73.3% of Thoroughbreds compared to the homozygous Arg/Arg and Pro/Pro that was detected in 17.1% and 9.6% of mares, respectively. The Arginine/Proline genotype was significantly associated with abortion (P=0.02), while Proline/Proline mares had a lower probability of abortion (P<0.05). These results indicate that p53 may play a role in equine reproduction. The second paper analyzed a single nucleotide polymorphism (SNP) in the p53 gene, looking for associations with reproductive parameters in Thoroughbred mares. This is the first study demonstrating the Arginine/Proline SNP in equine exon 4 p53 gene. The heterozygous Arginine/Proline was found in 73.3% of Thoroughbreds compared to the homozygous Arg/Arg and Pro/Pro that was detected in 17.1% and 9.6% of mares, respectively. The Arginine/Proline genotype was significantly associated with abortion (P=0.02), while Proline/Proline mares had a lower probability of abortion (P<0.05). These results indicate that p53 may play a role in equine reproduction. The third article has determined the presence of circulating cell-free fetal DNA (ccffDNA) in pregnant mare s plasma, looking to develop a molecular test for the prenatal diagnosis of fetal sex determination using SRY gene amplification by PCR, reamplification by PCR (2nd-PCR) and real-time quantitative PCR (qPCR). This is the first report of ccffDNA in equine species. The molecular sexing test resulted in sensitivity of 72% and accuracy of 85% on the PCR. Using the 2nd-PCR and qPCR we obtained an increasing in the sexing sensitivity results (90.9%) and an accuracy of 95%. This study demonstrates for the first time the fetal sex determination in mares using ccffDNA. This PhD thesis resulted in the publication of three papers in international journals of reproduction and a patent application request. The results presented here collaborate to understand the equine reproductive biology, and indicate potential genetic markers to fertility parameters.